The Pneumococcus Urinary Antigen Test Kit: Use in the laboratory for the presumptive diagnosis of pneumococcal bacteraemia - Tootla, Hafsah Deepa (Division of Medical Microbiology, 2021)
Introduction: Culture remains the ‘gold standard' for diagnosis of Streptococcus pneumoniae bacteraemia. Time to definitive identification using culture is 24–48 hours, and prior antibiotic therapy, the ability of S. pneumoniae to self-autolyse and its fastidious nature can yield no growth on culture. Novel detection methods for invasive pneumococcal disease include PCR and antigen tests. We evaluated using a urine antigen test directly on selected blood cultures with appropriate Gram stain results, immediately after signalling positive for the rapid identification of S. pneumoniae bacteraemia. Method: We collected 212 blood cultures that had signalled positive with an automated blood culture system, and then yielded gram-positive cocci in pairs/chains or cocci with uncertain morphological arrangement. The BinaxNOW Streptococcus pneumoniae urinary antigen test, routine culture with optochin and real time lytA PCR was performed on all samples. Diagnostic accuracy analysis (sensitivity and specificity) of the antigen test and Gram stain with gram-positive cocci in pairs was each compared to culture positivity for S. pneumoniae, PCR positivity and the composite of culture or PCR positivity for S. pneumoniae as the reference standards. Results: S. pneumoniae (Spn) was cultured in 55 samples, gram-positive organisms other than S. pneumoniae (NSpn) in 140 samples and 17 samples had no growth (NG). Grampositive cocci in pairs was predominant on Gram stain in the Spn/NG groups whilst the minority in the NSpn group. In the Spn group, all except 1 sample which was antigen positive but PCR negative, were antigen and PCR positive. In the NSpn group, antigen and PCR was negative in 123 samples, antigen and PCR positive in 1 sample and antigen positive but PCR negative in the remaining 16 samples. In the NG group, antigen and PCR were positive in 16 samples and antigen positive but PCR negative in 1 sample. Sensitivity of the antigen test compared to culture, PCR or the composite of culture or PCR was 100%. Specificity was 87-88% but increased to 93-96% when used in subsets with gram-positive cocci in pairs or clinical history compatible with respiratory illness or meningitis. Sensitivity and specificity of the antigen test when compared to Gram stain using gram-positive cocci in pairs (69%-75% and 81% respectively) were both higher. Discussion and Conclusion: Accurate and rapid diagnosis of S. pneumoniae bacteraemia is challenging with current diagnostic tools. Specificity of the antigen test is mostly limited by crossreactivity with viridans streptococci, coagulase negative staphylococci and enterococcus species, but this can be overcome if Gram stain morphology and clinical history is available. Sensitivity and specificity of Gram stain alone in predicting S. pneumoniae bacteraemia is poor and is increased with use of the antigen test. The antigen test is a useful adjunctive tool improving diagnosis and turnaround time of S. pneumoniae bacteraemia. In settings like ours, where high-level resistance, defined as minimum inhibitory concentration ≥2μg/mL to penicillin is still relatively low (~7%), rapid de-escalation to penicillin in the appropriate clinical setting would be possible with the introduction of such test and could also potentially be a suitable alternative to molecular testing for S. pneumoniae identification in samples with no growth on culture.